ANALYSIS OF SHARIA ECONOMIC LAW ON THE PRACTICE OF REDUCTION IN BANANA WEIGHING THROUGH EQUALIZATION METHODS A STUDY IN PEKON SANGGI BANDAR NEGERI SEMUONG DISTRICT TANGGAMUS REGENCY - Devita Anggraini Dinata; Muhammad Zaki Zaki; Herlina Kurniati Kurniati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the practice of equalized weight deductions in banana trading transactions in Pekon Sanggi, Bandar Negeri Semuong District, Tanggamus Regency. The study aims to analyze the application of a uniform deduction of one kilogram to each banana bunch and evaluate its conformity with the principles of Sharia Economic Law. This research employed a qualitative field research approach through observation, interviews, and documentation involving three banana farmers, one collector, and one community leader. The findings reveal that a deduction of one kilogram is uniformly applied to all banana bunches despite significant differences in their actual weights. Although the deduction mechanism is known and accepted by both parties, its implementation creates disproportionality because smaller banana bunches receive a higher percentage deduction than larger bunches. From the perspective of Sharia Economic Law, this practice raises concerns regarding justice, proportionality, and transparency and may potentially contain an element of gharar due to the absence of a proportional basis for determining deductions. Therefore, a more proportional deduction mechanism is needed to ensure fairness and balance in agricultural trading transactions.